EXPLORING ATTITUDES TOWARDS STUDENT ICT USE IN LUKUNGA DISTRICT PRIMARY SCHOOLS - Benjamin MANDA KISIMBA; Eustache BANZA NSOMWE-A-NKUNKWA; Francis ADAMS (Analele Universităţii din Craiova. Psihologie, Pedagogie)
This quantitative study explores the attitudes of school principals, teachers, and parents towards students' use of ICT during and after class time in primary schools across Lukunga District, Kinshasa-the capital city of the Democratic Republic of Congo. Guided by the Technology Acceptance Model (TAM), the study focused on two core constructs: Perceived Usefulness (PU) and Perceived Ease of Use (PEOU), which framed the interpretation of findings. Data were collected through structured questionnaires administered to a sample of 75 teachers, 75 parents, and 5 school principals. The responses were coded and analyzed using Microsoft Excel 2019, where both descriptive statistics (frequencies and percentages) and inferential statistics (chi-square tests) were applied. The findings revealed an overall positive attitude among all stakeholder groups towards student ICT use both in and out of the classroom. Teachers emphasized that ICT use enhances students' motivation, makes lessons more engaging, and that the absence of ICT use may reduce students’ future competitiveness in the labor market. Parents acknowledged ICT as essential for knowledge acquisition, access to global information, and more effective learning processes. School principals supported the integration of ICT into key educational activities through an age-appropriate curriculum, and also highlighted the importance of parental involvement at home as a complement to school-based ICT use. These insights contribute to understanding the enabling factors and potential barriers to ICT adoption in primary education, and inform policy and practice aimed at enhancing digital learning environments.